Development of Flashcard Use with QR Code to Teach Vocabulary for Fifth Grade Students in SD Negeri Modangan 03 - Ashari, Arif Maulana; Syaifudin,, Ahmad; Widiarini, Widiarini; Mubarok, Tyas Alhim (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
Language is a very important thing to learn to be used in everyday communication. In learning a foreign language, vocabulary learning is one of the things that has a significant role. This is because vocabulary is the basis for making a sentence that can then be used for communication both in writing and orally. In an unstructured interview conducted by the researcher with teachers and students of grade 5 at SD NEGERI MODANGAN 03, the researcher found an interesting problem. The teacher who teaches English in grade 5 of SD NEGERI MODANGAN 03 does not come from an English Education background, so she has difficulty finding effective media to teach English in class other than using student worksheets. Students have difficulty learning English because they do not know the meaning of the words on the student worksheets. Thus, the researcher decided that the purpose of this study was to develop teaching media that can help teachers in teaching vocabulary to 5th grade students of SD NEGERI MODANGAN 03. The research model used in this study is the ADDIE Model developed by Michael Molenda in 2015. There are 5 stages in this research process, namely Analysis, Design, Development, Implementation, and Evaluation. The media chosen by the researcher is Flashcard using QR Code to teach vocabulary. The results of this study can be seen from the N-Gain score of 58% which indicates that the learning media used is effective and provides good results. In addition, the average response value from students to the teaching media used is 88.5% which indicates that the teaching media used is able to increase students' interest and motivation in learning English.